2022
DOI: 10.3389/fbioe.2022.841591
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Nanobowl-Based Nest-Like Nanofiber Structure Prepared at Room Temperature and Pressure Promotes Osseointegration of Beagle Implants

Abstract: Nest-like nanofiber structures have potential applications in surface modifications of titanium implants. In this study, nest-like nanofiber structures were prepared on a titanium surface at room temperature and pressure by using the nanobowl template-assisted method combined with alkali etching. The characterization and biocompatibility of this material were analyzed by cellular adhesion, death, CCK-8, ALP, and RT-PCR assays in vitro, and osseointegration was evaluated by micro-CT and fluorescent labeling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…After anodization twice, the NT surface showed better cell adhesion performance than the PT surface (Figure 3D), indicating that a rough surface is conducive to cell adhesion, consistent with previous results. [ 50 ] This increased expression was further enhanced after loading with cinnamaldehyde, indicating that the introduction of cinnamaldehyde is conducive to cell spreading and adhesion. Furthermore, the images obtained by SEM intuitively showed that the cell morphology within 24 h of the NT treatment was significantly more extensive than that of the PT treatment; additionally, the cell morphology and state were more ideal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After anodization twice, the NT surface showed better cell adhesion performance than the PT surface (Figure 3D), indicating that a rough surface is conducive to cell adhesion, consistent with previous results. [ 50 ] This increased expression was further enhanced after loading with cinnamaldehyde, indicating that the introduction of cinnamaldehyde is conducive to cell spreading and adhesion. Furthermore, the images obtained by SEM intuitively showed that the cell morphology within 24 h of the NT treatment was significantly more extensive than that of the PT treatment; additionally, the cell morphology and state were more ideal.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, more bioactive substances of various sizes, including natural compounds, small molecule drugs, and active proteins, can be loaded. [49,50] Once cinnamaldehyde is loaded, the drug molecules quickly enter the inside of the nanotube aperture and induce a cloud-like change on the surface, indicating effective loading of the drug. This structure exhibited a much more efficient cinnamaldehyde adsorption capacity than traditional single-layer nanotubes [51] under a scanning electron microscope (Figure 2A).…”
Section: Fabrication and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…From a biomimetic perspective, micro/nano textured surface can mimic the structure of bone tissue and enhance cell responses. The micro/nano hierarchical architecture has been accounted to accelerate cell functions by synergistic equilibrating between cellular proliferation and differentiation ( Srivas et al, 2019 ; Sun et al, 2022 ). Studies have shown that it is possible to create hierarchical textures through the combination of micro and nano features on the same surface.…”
Section: Strategies Of Surface Topology Modificationmentioning
confidence: 99%
“…This might be based on a stepwise degeneration of the adhesive followed by sufficient osseointegration [36]. Other innovations focus on nest-like nanofiber structures to modify titanium implant surfaces and have been reported to improve osseointegration in animal models [37]. With respect to clinical conditions with a reduced bone turnover, such as osteoporosis, zinc-and strontium-modified implant surfaces showed an improved osseointegration in vivo [38].…”
Section: Introductionmentioning
confidence: 99%